Da geração 80 na arte contemporânea brasileira: profissionalização e permanência no ambiente artístico paulista - Monteiro, Fabiana Della Coletta (2016)
The research aims to shed a light on the Brazilian artistic production since the 1980’s, influenced by the country’s political opening after the military dictatorship and by the cultural movements resulted this period, focused on the dynamic of arts in the city of Sao Paulo. The arrival of a new generation on the art scene, called by the circuit as “Geração 80”, seems to have provoked a sense of rupture with the previous generation’s artistic production, mostly because of the use of traditional art medias, like painting, draws and sculpture. This work combines three fronts of theoretical and methodological analysis that aim to enlighten the senses and the acting of these artists in the city of Sao Paulo, mostly emerging from art schools and take positions as continuity in the art process. It presents the study of generations, which assumes by the historical context the heritage left by the previous generation in what was absorbed as a directional principle to the artistic production of the period and also to the principles that have been denied, that is, the character of rupture of this new generation and the internal conflicts of this group, especially with regard to construction of generational identity. Also the development of collective and social profile biography, and the trajectories of active Sao Paulo artists from the 1980s who now constitute a part of what we call contemporary art. And finally the fortune critical reception of this generation in the field of art, such as the inclusion signs and categories mobilized by critics as the legitimacy strategies of this production We investigate the social dispositions of the agents that act in the field of art for the production of context and sense in the Brazilian cultural scenario